Fabrication of anisotropically aligned nanofibrous scaffolds based on natural/synthetic polymer blends reinforced with cellulose nanocrystals for tendon tissue engineering - Domingues, Rui Miguel Andrade (2016)
[Excerpt] Introduction: Tendon disorders and injuries are among the most common musculoskeletal problems and their regeneration after injury remains a significant challenge. Given the prevalent fibrous nature of tendons’ ECM, which exhibits an aligned and hierarchical organization in structures from the nano to the macro scale, uniaxial aligned electrospun nanofibers produced from natural/synthetic polymer blends are among the most successful tendon scaffolds in tissue engineering (TE) strategies[1]. These biomaterials can provide the topographical cues to direct cell adhesion and proliferation, as well as positively affecting cell’s differentiation, phenotype maintenance and matrix deposition. However, the limited mechanical properties of electrospun biomaterials restrict their potential application in this field. In the present study, we propose the use of cellulose nanocrystals (CNCs), the “nature carbon nanotubes”, as a strategy for the reinforcement of electrospun polyɛcaprolactonechitosan (PCLC) nanofiber scaffolds without compromising their biological performance and thus expand their potential range of application in tendon TE strategies. (...)